An Overview of Diabetes Management in Schizophrenia Patients: Office Based Strategies for Primary Care Practitioners and Endocrinologists - Aniyizhai Annamalai; Cenk Tek (International Journal of Endocrinology)
Diabetes is common and seen in one in five patients with schizophrenia. It is more prevalent than in the general population and contributes to the increased morbidity and shortened lifespan seen in this population. However, screening and treatment for diabetes and other metabolic conditions remain poor for these patients. Multiple factors including genetic risk, neurobiologic mechanisms, psychotropic medications, and environmental factors contribute to the increased prevalence of diabetes. Primary care physicians should be aware of adverse effects of psychotropic medications that can cause or exacerbate diabetes and its complications. Management of diabetes requires physicians to tailor treatment recommendations to address special needs of this population. In addition to behavioral interventions, medications such as metformin have shown promise in attenuating weight loss and preventing hyperglycemia in those patients being treated with antipsychotic medications. Targeted diabetes prevention and treatment is critical in patients with schizophrenia and evidence-based interventions should be considered early in the course of treatment. This paper reviews the prevalence, etiology, and treatment of diabetes in schizophrenia and outlines office based interventions for physicians treating this vulnerable population.